Improving English Listening Skill Trough by Spotify Songs - Faisal Faisal; Anggraini Anggraini (Jurnal Sosial Humaniora dan Pendidikan, 2025)
In terms of global distribution, English is the most frequently spoken language. Therefore, in order to communicate at an international level, the student's communication abilities are required. There are numerous approaches to improve language skills, each with its own distinct set of characteristics. The development of music streaming apps such as Spotify ushered in a new way of listening to music. Daniel Ek and Martin Lorentzon founded Spotify in 2008. Spotify was called after a sentence that Ek and Lorentzon randomly blurted. Ek misheard the phrase "Spotify," and they assume the name is a play on "spot" and "identify". Spotify is a music and audio streaming service that offers copyrighted songs and podcasts. Spotify, as well as other English courses, were extremely effective in enhancing students' listening skills. This study can be used with other multimedia to enhance students' listening abilities. The goal of this research was to investigate students' perceptions of Spotify. This study employed a qualitative descriptive method, with data obtained via semi-structured interviews with ten respondents